Sistem fonetik dalam bahasa Bugis - Ahmad Rifani Talaohu (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2019)
Buginese language or Bahasa Bugis is the language of people who inhabited in the Celebes (Sulawesi) island, eastern part of Indonesia, which is exactly in South Sulawesi province. Buginese has affiliation with Austronesian language family that spreads into the several parts of the province, such as Bone, Pinrang, Soppeng, Parepare, Sidrap, Barru, Sinjai and Sengkang. Buginese has roughly 3.6 million native speakers which is the largest among any other three ethnic groups in South Sulawesi; Makassar, Mandar, and Toraja. This paper aims to examine the phonetics system of this largest active language in South Sulawesi. Simply put, this article will identify the consonants and vowels which exist in Buginese language and analyse the occurrence of those consonants and vowels.